Projects with young learners - Phillips, Diane; Burwood, Sarah; Dunford, Helen (Oxford Oxford university press, 2010)
Resource book for teachers give guidance on the key aspects of language teaching, and provide examples and discussion of actual classroom materials and techniques. Projects with young learners contains practical, tried and tested ideas and materials for planning, organizing, and carrying out project work with children aged 5 to 13.
Contents, indexes.
Keywords: Language; Learning; Activities; Games; English - foreign language; Teaching